Physical rehabilitation. Contemporary issues - Shakhlina L.G. (Pedagogìka, Psihologìâ ta Mediko-bìologìčnì Problemi Fìzičnogo Vihovannâ ì Sportu, 2012)
An analysis of recent literature on the co-temporal aspects of physical rehabilitation. It is shown that physical rehabilitation is one of the main places in the medical rehabilitation and is based on extensive use of physiotherapy - treatment of motion - by means of physical culture (physical therapy cultural organization). A brief historical aspect of the application of physical activity as a prophylactic or therapeutic purposes. The examples of modern usage in clinical practice in physical therapy for diseases, respiratory system, endocrine pathology, obstetric practice, for diseases and injuries of the musculoskeletal system, including in sports. It is shown that, unfortunately, but still insufficient kinesitherapy popular in medical practice. Not enough attention is paid to the process of physical rehabilitation of the individual approach, mainstreaming gender and age. An important aspect of the need for the physical rehabilitation is its use in treating children and adolescents, thereby drawing attention to the restoration of the lost opportunities of the young patient, but not to its shortcomings. Physical rehabilitation, practically, is accompanied by psychological rehabilitation, involving the patient to actively participate in his treatment, creating a motivation to favorable outcome.